Cardiopulmonary exercise testing and second-line pulmonary function tests to detect obstructive pattern in symptomatic smokers with borderline spirometry - Di Marco, Fabiano; Terraneo, Silvia; Job, Sara; Rinaldo, Rocco Francesco; Sferrazza Papa, Giuseppe Francesco; Roggi, Maria Adelaide; Santus, Pierachille; Centanni, Stefano (Respiratory medicine, 2017)
The need for additional research on symptomatic smokers with normal spirometry has been recently emphasized. Albeit not meeting criteria for Chronic obstructive pulmonary disease (COPD) diagnosis, symptomatic smokers may experience activity limitation, evidence of airway disease, and exacerbations. We, therefore, evaluated whether symptomatic smokers with borderline spirometry (post-bronchodilator FEV1/FVC ratio between 5th to 20th percentile of predicted values) have pulmonary function abnormalities at rest and ventilatory constraints during exercise. 48 subjects (aged 60 ± 8 years, mean ± SD, 73% males, 16 healthy, and 17 symptomatic smokers) underwent cardiopulmonary exercise testing (CPET), body plethysmography, nitrogen single-breath washout test (N2SBW), lung diffusion for carbon monoxide (DLCO), and forced oscillation technique (FOT). Compared to healthy subjects, symptomatic smokers showed: 1) reduced breathing reserve (36 ± 17 vs. 49 ± 12%, P = 0.050); 2) exercise induced dynamic hyperinflation (−0.20 ± 0.17 vs. −0.03 ± 0.21 L, P = 0.043); 3) higher residual volume (158 ± 22 vs. 112 ± 22%, P < 0.001); 4) phase 3 slope at N2SBW (4.7 ± 2.1 vs. 1.4 ± 0.6%, P < 0.001); 5) no significant differences in DLCO and FOT results. In smokers with borderline spirometry, CPET and second-line pulmonary function tests may detect obstructive pattern. These subjects should be referred for second line testing, to obtain a diagnosis, or at least to clarify the mechanisms underlying symptoms. Whether the natural history of these patients is similar to COPD, and they deserve a similar therapeutic approach is worth investigating. •Symptomatic smokers with normal spirometry deserve investigations.•Symptomatic smokers with normal spirometry may show an obstructive pattern.•Symptomatic smokers should be referred for second line testing.